Effect of growing media combined with biofertilizers on growth and survival of air-layered water apple (Syzygium samarangense L.) - Giriprasath, R S; Umesh, B C; Jeevitha, D; Vinay, T V; Sajan, K; Bharanidharan, A; Krishna, P Y; Jervin, A S R (Plant Science Today, 2026)
The present study was conducted to evaluate the influence of various biofertilizer-enriched potting media on the survival and growth performance of air-layered saplings of water apple (Syzygium samarangense L.) under tropical conditions. Mature shoots from 2-year old trees at the Karunya Institute of Technology and Sciences (KITS), Coimbatore, were air-layered using IBA at 2000, 3000 and 4000 mg L-1 concentrations, with sphagnum moss and cocopeat as rooting media during August to October, 2022. Successfully rooted layers were transplanted into 7 different potting mixtures consisting of soil, sand and farmyard manure (FYM) (1:1:1) either alone (control) or amended with various biofertilizers including Trichoderma viride, vermiwash (1 %), humic acid, Azospirillum brasilense, plant growth-promoting rhizobacteria (PGPR) and vesicular-arbuscular mycorrhiza (VAM). The study was conducted using a randomized complete block design (RCBD) comprising 3 replications. Plant height, leaf number, shoot number, root parameters and survival percentage were observed at 30, 60 and 90 days after potting (DAP). Results revealed that potting media enriched with vermiwash - 1 % (T₃) significantly outperformed other treatments, showing the highest survival rate (100 %) and superior root attributes, including root length (21.80 cm), primary roots number (43.35), secondary roots number (89.17) and primary root diameter (3.50 mm) at 90 DAP. The study concludes that the integration of vermiwash with a soil, sand and FYM base enhances the survivability and root development of water apple air layers, offering a promising technique for efficient propagation under tropical nursery conditions.